2016
DOI: 10.1111/jpn.12433
|View full text |Cite
|
Sign up to set email alerts
|

Can breeder reproductive status, performance and egg quality be enhanced by supplementation and transition of n‐3 fatty acids?

Abstract: The aim of this experiment was to investigate the effect of n-3 fatty acid (FA) supplemented diets on breeder performance, productivity and egg quality. Breeders (n = 480) were fed the supplemented diet from 18 weeks onwards; the inclusion level of n-3 FA was increased from 1.5% to 3.0% from 34 weeks of age onwards until 48 weeks of age. Ross-308 broiler breeders (n = 480) were fed one of four different diets: a basal diet rich in n-6 FA (control diet) or one of three diets rich in n-3 FA. For the n-3 FA diets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Feeding hens n−3 FA–rich feedstuffs (such as flaxseed, marine sources) has become one of the most popular and sustainable means for supplying affordable n−3 FA–fortified eggs for human consumption ( Elkin et al., 2015 ). Several studies have shown that feeding broiler breeder with diets containing n−3 FA sources enriched yolk with n−3 FA ( Cherian, 2015 , Koppenol et al., 2015a , Koppenol et al., 2015b , Delezie et al., 2016 ). However, there is little information on the effects of feeding egg-type chick breeder diets with n−3 FA sources on the composition of fertile eggs and embryonic uptake of FA.…”
Section: Introductionmentioning
confidence: 99%
“…Feeding hens n−3 FA–rich feedstuffs (such as flaxseed, marine sources) has become one of the most popular and sustainable means for supplying affordable n−3 FA–fortified eggs for human consumption ( Elkin et al., 2015 ). Several studies have shown that feeding broiler breeder with diets containing n−3 FA sources enriched yolk with n−3 FA ( Cherian, 2015 , Koppenol et al., 2015a , Koppenol et al., 2015b , Delezie et al., 2016 ). However, there is little information on the effects of feeding egg-type chick breeder diets with n−3 FA sources on the composition of fertile eggs and embryonic uptake of FA.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of lipid sources in the diet of quails can be seen as a breakthrough in animal nutrition, receiving much attention from all segments of the poultry industry (Delezie et al ., 2016; Lee et al ., 2019). The feed provided to the quail can change the physical quality of the eggs such as size, percentage of components and shell strength, in addition to influencing the nutritional quality of the eggs (Bruneel et al ., 2013; Secci et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%